Half day seminar on social interaction for librarians (9th April 2010) - Suja', Balqis (Persatuan Pustakawan Malaysia, 2010)
This is a report of a seminar that highly elaborated on the need of shared values for the professional and social interaction ethics. Beside awareness on avoiding a mechanical lifestyle, participants were enlightened with the idea of developing intelligences to enhance their value as a person and their image as a librarian.